Serum S-100 beta response to exercise-heat strain before and after acclimation - Cheuvront, S. N.; Chinevere, T. D.; Ely, B. R.; Kenefick, R. W.; Goodman, D. A.; McClung, J. P.; Sawka, M. N. (Medicine & Science in Sports & Exercise, 2008)
Exercise alone or in combination with environmental heat stress can elevate blood S-100Beta protein concentrations. However, the explanatory power of exercise with marked environmental heat stress on the appearance of S-100[beta] is questionable. It is possible that the process of heat acclimation might afford additional insight.